Budowanie tożsamości przez nauczyciela - Kabat , Małgorzata (Studia Edukacyjne, 2020)
The article attempts to capture the complexity of explanations concerning the teacher’s identity. Attention is paid to various dimensions and learning to build this identity in various spaces of the contemporary teacher’s life and work. It considers these spaces from the position of I. Menter’s concept that includes two sustainable areas: individual and institutional. In each of them there are metacognitive processes and meta-insights, necessary to construct a mature teacher’s identity. The teacher’s acquired knowledge and experience enriches the ability of individual learning as well as learning in the workplace, while serving the effective functioning and education of others in dynamically changing educational conditions.